Cinema na internet : espaços informais de circulação, pirataria e cinefilia - Meili, Angela Maria (2015)
This research analyses the phenomenon of informal film circulation on Internet, building a systematic orientation within the vast universe of distribution networks. Piracy is a cultural activity that corresponds to a range of collective interests of global dimension and relates to regulatory policies, critical intellectual property, civil disobedience, market, technological innovations participatory culture and informal economies. This study explores the relations between BitTorrent networks, cinema distribution and ciber-cinephilia, pointing to networks with hybrid nature, where informal and formal media converge, technical elements combine, niches and global cultures dialogue, moral sensibilities-relativize, speeches, daily practices and political actions are developed and where markets are transformed. We have shown that, within the space of unauthorized circulation, specialized distribution hubs have their own symbolic dimension, which manifest particular senses about cinema, under the influence of a movie buff and multicultural imaginary.